A Conceptual Framework of Bacterial Foraging Optimization Algorithm for Data Classification - Hossin, M.; Mohd Suria, F. (2016)
Most previous works on Bacterial Foraging Optimization Algorithm (BFOA) for data classification were integrated BFOA as a feature selection algorithm and parameters optimizer for other classifiers. To the best of our knowledge, no effort has been carried out to fully utilize BFOA as a classifier. This paper presents a conceptual framework of instance-based BFOA. The proposed conceptual framework is designed based on the prototype searching approach whose target is to obtain an optimal reference set (cardinality) and simultaneously aim for high generalization performance by utilizing the strengths of BFOA.